Revival of monophasic contrast injection protocols: superiority of a monophasic injection protocol compared to a biphasic injection protocol in high-pitch CT angiography. (October 2016) - Apitzsch, Jonas; Jost, Gregor; Bonifer, Elisabeth; Keulers, Annika; Pietsch, Hubertus; Mahnken, Andreas Horst
Background: Biphasic injection protocols are frequently used because they yield homogenous contrast enhancement. We hypothesize that with faster scanners and shorter scan times, biphasic injection protocols are no longer necessary. Purpose: To evaluate whether a monophasic injection protocol is equivalent to a biphasic protocol in terms of contrast enhancement and homogeneity. Material and Methods: Repeated high-pitch CTA (pitch 3) and conventional standard-pitch computed tomography angiography (CTA) (pitch 1.2) from the cervical region to the symphysis was performed in seven beagles (11.2 ± 2.5 kg) in a cross-over study design. Arterial contrast enhancement was measured along the z-axis in the ascending, descending, and abdominal aorta and the iliac arteries. The z-axis is the longitudinal axis of the human body and at the same time the direction in which the CT table is moving. The data were analyzed using repeated measures ANOVA with a post-hoc t-test and visual assessment of the scans. Results: In high-pitch CTA, monophasic injection protocols were superior to biphasic injection protocols in enhancement levels ( P < 0.05) and enhancement homogeneity along the z-axis ( P < 0.05). In conventional CTA, enhancement levels did not differ. Contrast homogeneity was better for biphasic protocols. Conclusion: High-pitch CTA monophasic injection protocols are superior to biphasic injection protocols, due to a higher and more homogeneous contrast enhancement with the same amount of contrast medium used.